The good, the bad, and the ugly of consumer sleep technologies use among athletes: A call for action - Trabelsi, K.; BaHammam, A. S.; Chtourou, H.; Jahrami, H.; Vitiello, M. V. (Journal of Sport and Health Science, 2023)
For athletes, the quality and quantity of sleep are essential elements for optimizing recovery and subsequent performance. Unfortunately, athletes frequently face challenges getting sufficient, high-quality sleep. A recent systematic review and meta-analysis of 81 studies involving 1830 athletes concluded that compared to healthy non-athletes, athletes' sleep duration was shorter with poorer sleep efficiency.3 Notable sleep issues (e.g., sleep apnea and snoring, as well as insomnia and trouble falling asleep) were revealed in young athletes. It was common for sleep quality and architecture to change over time depending on the training period.